No Pregnancy, No Marriage: Unveiling the Ideology Behind the Discourse of ‘Sing Beling Sing Nganten’ in Balinese Marriage Culture - Luh Gede Sukardiasih; I Nyoman Weda Kusuma; Evalina Franciska Hutasoit (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
In Bali “sing beling sing nganten” phenomenon literally meaning where a couple gets married only after the bride is pregnant, often to prove her fertility, continues to shape community views on marriage and gender. Although the research was conducted in Tabanan Regency, the phenomenon is largely similar and occurs throughout Bali; therefore, the choice of location does not produce substantive differences in the findings. This study explores the ideologies embedded in “sing beling sing nganten" discourse and how it sustains unequal power relations within marriage and culture. Using qualitative methods and a critical discourse analysis approach, the research identifies four dominant ideologies underpinning the discourse. First, ideology emphasizes lineage and ancestral spiritual continuity. Second, bodily ideology constructs women’s bodies as both autonomous and objectified. Third, fertility ideology reinforces women’s reproductive roles and health. Fourth, common-sense ideology normalizes social acceptance toward this discourse. The study reveals that “sing beling sing nganten” lacks an objective basis of truth and functions primarily to legitimize male power over women.